Navigating tenor and bass clefs in Sonata in E Minor, Antonio Vivaldi Alexander Debrus / Muhammad Haiqal Aydiel Zulkefli - Zulkefli, Muhammad Haiqal Aydiel (2022)
Navigates tenor and bass clefs one of preparation that every musician needs to be prepare. There are many steps that musicians need to prepare in order to navigates tenor and bass clefs including sight reading, analyse score, how to start navigates and many more. It shows that navigates tenor and bass clefs is important in order to rehears, practicing and also performing. My research will help a musician or more important will helps cellist to navigates tenor and bass clefs. This study aims to navigates tenor and bass clefs and the position that Alexander Debrus used in Sonata in E minor by Antonio Vivaldi.